Berenstain Bears (The)/ : On the moon - Berenstain, Stan (New York : Beginner Books, 1985)
Two Berenstain Bears and their pup take a rocket ship to the moon.
Keywords: Moon - Exploration -- Fiction; Bears -- Fiction; Stories in rhyme